Recuperação por meio do sentido da vida: uma pesquisa sobre as contribuições da Logoterapia no processo de busca pela independência química - Marlo Margarida, Daniel (Vox Scripturae - Revista Teológica Internacional, 2013)
This academic work is a research about the therapeutic aspects of Logotherapy applied to the reality of drug dependence. Firstly, the research introduces the problematic issue starting with questions of existential relevance to the drug dependant, with the objective of answering these previous investigations. After, it is elaborated a general framework with the main concepts, considerations, criteria and classifications of drug dependence, in order to provide a general overview on the subject. In the research is identified the historical context of emergence from this  Psychotherapy school at same time it is done the analysis of the brief biographical aspects of Victor Emil Frankl. The study also presents in a concise manner the anthropological differences, which there are among the  Psychoanalysis by Sigmund Freud, the Individual Psychology by Alfred Adler and the ones taught by the author Victor E. Frankl. Then, it is organized a synthesis of the Logotherapy thinking explaining its fundamental concepts. In addition, in the research has been made  intense reference to the original sources interconnecting the themes that compose it. As a result, the study  investigates textual tests which demonstrate the relationship between the incidence of drug dependence and the lack of  meaning in  life. To conclude, this scientific study answers the initial questions through a reading based on the works researched previously, proposing a way of expressive interpretation which is potentially effective to the drug dependence recuperation process.
Keywords: Drug dependence; Work; Love; Suffering; Meaning of life; Recuperation; Self actualization; God